History of cheese and cheese making - Keskin, Hilal (IGI Global, 2024)
This chapter addresses the historical development and cultural significance of cheese making. It examines the emergence of cheese in the Near East, Mediterranean, and Central Europe from the Neolithic Age and details the initial cheese production techniques and materials used. The chapter discusses the evolutionary processes in the production and consumption of cheese during ancient and medieval periods, the preservation of local and traditional cheese varieties, and the transition to industrial production. Additionally, the role of cheese in contemporary gastronomic tourism and the concept of cheese tourism are explored. Highlighting the historical and cultural importance of cheese, this study explains its development as a global food commodity and its role in the modern world.
Keywords: Neolithic Age; Middle Ages; Central Europe; Cheese Tourism; Roquefort